Unlocking the mystery of internal investigation: the use of information from private internal investigations in the Polish criminal process - Andrzej Sakowicz; Sebastian Zieliński (Revista Brasileira de Direito Processual Penal, 2023)
This study aims to present the problems associated with the use of information from private internal investigation in a criminal process. The paper first presents the essence, functions, limits, and purposes of internal investigations, taking into account legal restrictions, including constitutional ones. Further in the paper, the authors critically analyze the possibility of using materials obtained and produced in internal investigations in criminal proceedings. A significant number of internal investigations are conducted by attorneys. Therefore, the paper also evaluates the permissibility of abolishing the attorney-client privilege and of the court or the law enforcement agencies obtaining the materials produced by an attorney in the course of an internal investigation or questioning of the lawyer. Having an attorney conduct an internal investigation improves the security of the information produced in the course of the internal investigation, as the materials are covered by the attorney-client privilege. However, one should bear in mind that in Poland this is not an absolute protection. The considerations led the authors to the conclusion that internal investigations are a valuable tool of the system for preventing irregularities in corporations and an important source of materials that can be used in criminal proceedings.